Electrochemistry of metal complexes : applications from electroplating to oxide layer formation - Survila, Arvydas (Wiley-VCH, 2015)
This book aims to sequentially cover all the major stages of electrochemical processes (mass transport, adsorption, charge transfer), with a special emphasis on their deep interrelation. Starting with general considerations on equilibria in solutions and at interfaces as well as on mass transport, the text acquaints readers with the theory and common experimental practice for studying electrochemical reactions of metals complexes. The core part of the book deals with all important aspects of electroplating, including a systematic discussion of co-deposition of metals and formation of alloys.